Autophagic Reprogramming of Macrophages Polarization - Mazher, Mayada Mahmoud Zaki Mohamed (AUC Knowledge Fountain, 2021)
Background: Macroautophagy is a highly conserved catabolic process among eukaryotes. Autophagosome is a piece of double-membrane machinery that fuses with lysosomes to form autolysosomes. Autolysosome degrades organelles and organizes the pathogen engulfment during phagocytosis in innate immunity. Macrophages are highly dynamic immune cells that orchestrate the host-pathogen interaction. Interestingly, autophagy is implicated in disease pathophysiologies such as Crohn’s disease, cancer, and neurodegenerative diseases. Therefore, this work aimed to study the interplay between autophagy and macrophage polarization (activation) through two approaches, first to construct the genetic regulatory network and pathway analysis. And to predict the target proteins that mediate the interplay between autophagy and macrophage activation(polarization). Followed by an in vitro experimental validation of target proteins using immune co-localization studies, flow cytometry studies, laser confocal microscopy studies, and gene expression analysis. Methods: A systems biology approach was performed to find the interplay between Autophagy related genes (Atgs) & Differentially expressed genes of Macrophage Polarization M1-M2 (DEGs), followed by common pathway enrichment and construction of transcription factors and mi-RNAs regulatory networks. The Atgs and DEGs targets that mediate the interplay between autophagy and macrophage polarization were defined, and experimental validation for targets took place. Bone marrow-derived monocytes were isolated from the femur and tibia of female mice. After differentiation of monocytes to M0, M1, and M2a, the lineage phenotypes were characterized using flow cytometry. Afterward, we validated the targets of Smad1, LC3A&B, Atg16L1, Atg7, IL6, CD68, Arg-1, and Vamp7. Finally, we investigated the impact of autophagy inhibition on all immune lineages using autophagy inhibitor Bafilomycin-A. Results: Immune phenotyping by flow cytometry revealed three macrophage phenotypes: (IL6+/CD68+) M0, (IL6+/CD68+/Arg-1 +) M1 and (CD68+/Arg-1) M2a lineages. And 3D reconstruction of laser confocal microscopy Z-stalk images revealed an increase of autophagy activity in both M1 and M2a lineages. Besides, a significant increase was observed in pre autophagosome size and number of Atg-7, Atg-16L1 in interleukin -4 activated M2a cells compared to control M 0 naïve cells. The size of LC 3 A& B auto phagosomal aggregates showed an increase in M2a cells. RT qPCR supported these findings and showed the high gene expression profile of Atg 16 L 1- 3, Smad1, and Vamp 7 in M2a lineage. Bafilomycin –A, an autophagy inhibitor, induced increased expression of CD68 and Arg-1 in all cell lineages. Phagocytosis assay with Heat killed E Coli bacteria showed decreased phagocytosis activity in IL-4 activated M2a cells but not M1 cells. Conclusion: This study suggests that autophagy reprograms macrophages through CD68 and Arginase-1 phagocytosis markers and Atg 16 L 1 -3 dependent manner.